2008
DOI: 10.1590/s0103-50532008000500010
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence, photoabsorption and photoemission studies of hydrazone thin film used as hole transporting material in OLEDs

Abstract: A fotoluminescência de filmes finos de 1-(3-metilfenil)-1,2,3,4-tetrahidroquinolina-6-carboxialdeído-1,1'-difenilhidrazona foi monitorada em função da irradiação com luz UV. A intensidade da emissão decresce exponencialmente com o tempo de exposição, sugerindo degradação das amostras. Com o objetivo de investigar os mecanismos de degradação e determinar a estrutura eletrônica desse material orgânico usado com sucesso como camada transportadora de buracos na fabricação de diodos orgânicos emissores de luz (OLED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
1
5
0
1
Order By: Relevance
“…Therefore, the NPB reacts under extreme irradiation by ejecting nitrogen and benzene out from the molecule, i.e., by decomposing first at its weakest point, the C-N bond [10]. Similar results were also observed for the MTCD molecule investigated using synchrotron based photoabsorption and photoemission techniques [11].…”
Section: Methodssupporting
confidence: 68%
“…Therefore, the NPB reacts under extreme irradiation by ejecting nitrogen and benzene out from the molecule, i.e., by decomposing first at its weakest point, the C-N bond [10]. Similar results were also observed for the MTCD molecule investigated using synchrotron based photoabsorption and photoemission techniques [11].…”
Section: Methodssupporting
confidence: 68%
“…Similarly, Singh et al [5] synthesized the cobalt(II) complexes with somea cylhydrazones, which showed afair antifungal and antibacterial activity against anumber of fungi and bacteria. Otherwise, photoluminescence, photoabsorption and photoemission studies of hydrazone thin filmsused as hole transporting material in organic light emitting diodes (OLEDs) were reported [6].Onthe other hand, isoxazole compounds have arich history with both pharmaceutical and agricultural applications due to their apoptotic activity [7], plantgrowth regulating activity [8] and antibacterial activity [9]. In the title compound, C 12 H 11 N 3 O 3 ,the molecule is almost planar, the dihedral angle formed by the benzene and isoxazole rings is 2.03 (8) …”
Section: Discussionmentioning
confidence: 99%
“…A busca por polímeros condutores e por arquiteturas de dispositivos que resultem em maior eficiência, bem como por compostos dopantes resistentes aos processos de fabricação e que exibam propriedades eletroluminescentes desejadas, são desafios que têm alavancado as pesquisas nessa área. [108][109][110][111][112][113] Em um processo eletroluminescente, a população do estado excitado das moléculas de dopante ocorre pela recombinação de pares combinados elétron-lacuna via atração coulômbica na camada emissiva. A relaxação desses estados excitados leva à população de 25% de estados singletes (S 1 ) e 75% de estados tripletes (T 1 ) nas 114 Uma vez que esses compostos apresentam uma rápida e eficiente desativação a partir do estado excitado singlete, quando comparada à velocidade de cruzamento intersistema, nota-se que somente o estado singlete emite luz.…”
Section: +unclassified